Challenges, Prospects and Role of Insurance on Economic Growth in Bangladesh - Mohammad Ali (IIUM Journal of Case Studies in Management, 2020)
This paper aims to review the role of insurance on economic growth and to analyse challenges and prospects of insurance sector in Bangladesh. Based on the secondary data, this research critically reviews the previous studies to find the contribution of insurance on economic growth and prospects as well as challenges of insurance sector in the context of Bangladesh. Insurance has significant contribution on economic growth of a country that facilitates to create a strong capital base and gain economic independency. The study found that the key problems of this sector are deficiency of publicity, lack of qualified human resource, dearth of marketing policies, absence of business ethics, legal complexities, unskilled agents, poor IT support, insufficient return on investment, lack of transparency, lack of public awareness and traditional management. Therefore, initiating innovative marketing strategies, attracting and retaining talent, developing talent, increasing awareness, adapting information technology (IT), avoiding harmful competition, increasing return on investment, offering diversifies and attracting packages, adapting dynamic management style and implementing effective insurance policy are suggested to overcome the challenges of this sector.